EMPLOYEE PERFORMANCE AND INFLUENCING FACTORS - Hanung Eka Atmaja; Fera Nelfianti; Instianti Elyana (Jurnal Ekonomi, 2023)
Human resource management exists in a company to produce employees who are skilled at work because employees are a valuable asset to the company's operations and progress. Human resource (HR) management is required to ensure that all company activities and activities run smoothly and as expected. This study was carried out by distributing questionnaires in order to collect useful data for testing the research hypothesis. Employees of Bandung's People's Credit Bank (BPR) were given questionnaires. The findings of this study demonstrate that all research hypotheses are supported by test results. As dependents, all independent variables have a significant positive effect on employee performance.